2021
DOI: 10.3389/fpsyg.2020.597488
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship of Interoceptive Accuracy and Attention: A Controlled Study With Depressed Inpatients and a Healthy Cohort

Abstract: ObjectivePrevious research has shown reduced interoceptive accuracy (IAcc) in depression. Attention deficit represents a key symptom of depression. Moreover, IAcc is positively correlated with attention. There is no study that investigates the effect of depression on IAcc and attention. The aim of this study is to examine the mediating effect of IAcc on depression and attention.MethodsThirty-six depressed patients from the Psychosomatic Clinic in Windach were matched with 36 healthy controls according to age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Complementing and extending previous work ( Ferentzi, Horvath & Koteles, 2019 ; Schultchen et al, 2020 ; Ventura-Bort, Wendt & Weymar, 2021 ), the results of this study suggest that greater scores on the IAS (subjective interoceptive accuracy) corresponded to reduced negative affect and greater self-regard. Thus, as hypothesized, greater subjective accuracy is associated with liking oneself, in addition to reduced negative affect (the latter is discussed further below).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Complementing and extending previous work ( Ferentzi, Horvath & Koteles, 2019 ; Schultchen et al, 2020 ; Ventura-Bort, Wendt & Weymar, 2021 ), the results of this study suggest that greater scores on the IAS (subjective interoceptive accuracy) corresponded to reduced negative affect and greater self-regard. Thus, as hypothesized, greater subjective accuracy is associated with liking oneself, in addition to reduced negative affect (the latter is discussed further below).…”
Section: Discussionsupporting
confidence: 85%
“…No other study included measures of well-being or emotion, though Rae et al (2020) measured impulsivity and found no association with interoceptive attention. Schultchen et al (2020) found that visual attention and objectively measured IA were independently associated with depression (the authors did not include self-report measures of interoception). Haustein et al (2023) found similar patterns of associations in a sample of older adults.…”
Section: Introductionmentioning
confidence: 99%
“…However, Zamariola et al (2019b) found that interoceptive abilities did not modulate negative affect. In contrast, impaired interoceptive abilities were found in various mental disorders, such as anorexia nervosa ( Pollatos et al, 2008 ; Fischer et al, 2016 ), depression ( Pollatos et al, 2009 ; Eggart et al, 2019 ; Schultchen et al, 2021 ), somatoform disorders ( Weiss et al, 2014 ), obsessive-compulsive disorders ( Schultchen et al, 2019b ), or schizophrenia ( Koreki et al, 2020 ). However, it needs to be noted that evidence concerning the association between interoceptive abilities and somatic symptoms and related disorders (e.g., Mussgay et al, 1999 ; Scholz et al, 2001 ) as well as regarding anxiety or panic disorders (e.g., Domschke et al, 2010 ; Stevens et al, 2011 ; Krautwurst et al, 2016 ) is mixed.…”
Section: Introductionmentioning
confidence: 99%
“…Altered HEPs and cardiac reactivity to unpredictable negative events may be particularly relevant when modeling the relationships of interoceptive system dysfunction and atypical autonomic regulation with the risk of depression. Abnormal cardiac activity (32, 77, 78) and low interoceptive sensitivity (7981) have been widely documented in depressed patients, suggesting associations of depression with autonomic imbalance and interoceptive impairment. Our findings enhance understanding of this relationship, revealing that disturbances in autonomic cardiac functioning and the brain interoceptive network were also observed in healthy individuals with high BDI scores.…”
Section: Discussionmentioning
confidence: 99%